2018
DOI: 10.1055/s-0038-1666820
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implants and Children with Vestibular Impairments

Abstract: Sensorineural hearing loss (SNHL) in children occurs in 1 to 3% of live births and acquired hearing loss can additionally occur. This sensory deficit has far reaching consequences that have been shown to extend beyond speech and language development. Thankfully there are many therapeutic options that exist for these children with the aim of decreasing the morbidity of their hearing impairment. Of late, focus has shifted beyond speech and language outcomes to the overall performance of children with SNHL in rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 116 publications
1
12
0
Order By: Relevance
“…In a US public health survey, hearing loss increased the likelihood of reporting child behavioral diagnoses (55% for hearing loss, adjusted odds ratio [OR] for autism, 2.9; 95% CI, 1.8-4.9), problems with behavior (95% for hearing loss, adjusted OR for attention-deficit disorder, 3.1; 95% CI, 2.5-3.9), and difficulties with socioemotional domains (90% for hearing loss, adjusted OR, 3.9; 95% CI, 3.2-4.7) . In addition, 17% to 48% of children with unilateral hearing loss and 50% with cochlear implant have impaired vestibular function, which can further influence their ability to participate in normal childhood activities . Long-term longitudinal studies have found significant relationships between childhood hearing loss and decreased well-being and self-esteem as well as anxiety and depression among women …”
Section: Consequences Of Hearing Loss In Childrenmentioning
confidence: 99%
“…In a US public health survey, hearing loss increased the likelihood of reporting child behavioral diagnoses (55% for hearing loss, adjusted odds ratio [OR] for autism, 2.9; 95% CI, 1.8-4.9), problems with behavior (95% for hearing loss, adjusted OR for attention-deficit disorder, 3.1; 95% CI, 2.5-3.9), and difficulties with socioemotional domains (90% for hearing loss, adjusted OR, 3.9; 95% CI, 3.2-4.7) . In addition, 17% to 48% of children with unilateral hearing loss and 50% with cochlear implant have impaired vestibular function, which can further influence their ability to participate in normal childhood activities . Long-term longitudinal studies have found significant relationships between childhood hearing loss and decreased well-being and self-esteem as well as anxiety and depression among women …”
Section: Consequences Of Hearing Loss In Childrenmentioning
confidence: 99%
“…The rationale for vestibular screening at the age of 6 months is the following: (1) the hearing loss is confirmed in the majority of the children by that age 39 , (2) gross motor milestones can already give an idea of the child’s vestibular function 3 , and (3) most children have already developed sufficient head stabilisation due to sufficient development and control of neck musculature, which is fundamental for reliable cVEMP assessment 40 . In addition, possible cochlear implant surgery which entails a potential risk for vestibular (mainly otolith) deficits 31 , 41 43 , has not been performed yet 44 . As a result, the vestibular (mainly saccular) status is known before some of these children will undergo cochlear implant surgery.…”
Section: Introductionmentioning
confidence: 99%
“…This precise population endures a double sensory deficit, which means it is particularly at risk for developmental delays. To ensure better overall clinical management, potential vestibular disorders should be actively screened in children with hearing impairments, who are particularly at risk ( 5 ).…”
Section: Introductionmentioning
confidence: 99%